DETERMINANTS OF FINANCIAL REPORTING QUALITY: EVIDENCE FROM LISTED MANUFACTURING FIRMS IN NIGERIA (Journal of Global Accounting, 2023)
This paper investigates the determinants of financial reporting quality in Quoted manufacturing firms in Nigeria. In order to achieve the objectives of the study, a total of fifty-two (52) firms were selected based on a purposive sampling technique. The firms included in the sample had to meet two key criteria: first, they have electronic websites; and second, they had published annual reports in their websites for a period of seven successive years from 2012 to 2018. The study adopted the ex-post facto research design and used longitudinal data from secondary sources. The hypotheses were validated with the use of multiple regressions as a tool for data analysis. The results showed a positive significant relationship between firm age, firm size, Board size, Ownership structure and financial reporting quality, measured using residuals from the modified Jones model. It is recommended among others that firms may increase their size and leverage levels, which apart from enjoying the benefits of leverage; it provides an incentive to quality earnings reporting as seen in major research. A good corporate governance practices (code) should be maintained as it has been found not only to preserve the going concern of the firm but also a strong feature for enhancing the quality of financial reporting. The board size of between 5 and 11 is recommended as it has been found that this size is adequate to check earnings manipulation and other related financial statement fraud in the sectors. Emphasis should not be placed on the age of the firm, but on their capital tangibility and ability to checkmate management tendencies to manipulate financials reports or statement.
Keywords: Earnings Management; Financial Reporting Quality; Firm Characteristics; Corporate Governance